Pengaruh Keterikatan Konsumen terhadap Loyalitas Merek pada Konsumen Grab di Kota Makassar - MS, Fadhilah Nur Azhari; Bakar, Resekiani Mas (JURNAL PSIKOLOGI, 2024)
Brand loyalty on grab being a special concern because the growth of the needs on customers and others company innovation that can effect on online transportation company's performance and success. Brand loyalty can allegedly be influenced through consumer engagement. This study aims to determine the effect of consumer engagement on brand loyalty on grab consumers in Makassar City. The data in this study is that Grab consumers in Makassar City as many as 310 respondents through the google form. The measuring instrument used in this study is the scale of consumer engagement and brand loyalty. The data were analyzed using linear regression analysis techniques. The results showed that there is a positive influence between consumer engagement and brand loyalty. This research illustrates that the higher the consumer engagement, the higher the brand loyalty. This research can inform Grab to build strategy so they can maintain their customer and for the next researchers that consumer engagement can intervene in brand loyalty.